Turkey's 'Self' and 'Other' definitions in the course of the EU accession process - Saral, Melek (Amsterdam University Press, 2017)
While Turkey in recent years has experienced an exhaustive accession process to join the EU -a long desired aim-, at the same time it has been increasing its involvement across the Middle East, leading to a debate over whether it is altering its focus from West to East. This book reveals that a shift in focus can be seen through analysis of the Turkish political elites' definitions of "self" and "other" that were established as part of the EU accession process. Melek Saral uses these definitions to help us better understand the shift that Turkey is currently undergoing